P17.10 Hiv testing self-efficacy is associated with higher hiv testing frequency and perceived likelihood to self-test among gay and bisexual men. (13th September 2015) - Jamil, MS; Bavinton, B; Guy, R; Fairley, C; Grulich, A; Holt, M; Smith, K; Chen, M; McNulty, A; Conway, DP; Keen, P; Bradley, J; et al.
Abstract : Introduction: Regular testing of individuals at high risk of HIV is central to current prevention strategies, and crucial to decrease the time-to-diagnosis. Little research has been conducted on 'self-efficacy': the perceived ability to undertake HIV testing among gay and bisexual men (GBM). We examined self-efficacy in relation to HIV testing frequency and likelihood to self-test among GBM. Methods: Participants were HIV-negative GBM at increased risk of HIV (>5 partners or any condomless anal intercourse in previous 3 months) in a randomised controlled trial of HIV self-testing (FORTH). Participants completed a baseline survey at enrolment. We constructed a HIV Testing Self-Efficacy (HTSE) scale measuring confidence in one's perceived ability to undertake HIV testing comprising 8 items ('not at all confident' = 0 to 'completely confident' = 4; Cronbach's α = 0.81). Total HTSE score consisted of the sum of scores for all items. We determined the factors associated with HIV testing frequency in the past 12 months and perceived likelihood to self-test in the future using logistic regression. Results: A total of 355 GBM were included. Median age was 33 years (inter-quartile range [IQR] = 26–41), and 63% were Australian-born. Overall, 95% reported having previously tested for HIV, and 65% reported being 'very likely' to self-test for HIV. The median HTSE score was 26 (IQR = 23–29, range = 8–32). In multivariate analysis, factors independently associated with ≥3 HIV tests in past 12 months were: HTSE score (adjusted odds ratio [AOR] = 1.07 for one unit increase, 95% CI = 1.02–1.13, p = 0.011); and >10 partners in past 6 months (AOR = 1.85, 95% CI = 1.10–3.12, p = 0.020). Only HTSE score was associated with being 'very likely' to self-test (OR = 1.08, 95% CI = 1.03–1.13, p = 0.001). Conclusion: HIV testing self-efficacy is independently associated with testing frequency and likelihood to self-test. Improving GBM's confidence in HIV testing, by improving their knowledge and experience may lead to higher testing frequency. Future longitudinal analysis will provide information about the causal pathways between HTSE, testing frequency and actual self-testing measured in the trial. Disclosure of interest statement: The research is funded through a NHMRC Program grant from the NHMRC and self-test kits were purchased from OraSure Technologies Inc. (Bethlehem, PA, USA). The Kirby Institute and the Centre for Social Research in Health receive funding from the Australian Government Department of Health.